Electrochemical Double-Layer Capacitor Containing Mixtures of Ionic Liquid, Lithium Salt, and Organic Solvent as an Electrolyte - Li, Xiangyuan; Li, Hao; Feng, Rui; He, Long; Lu, Hai (Frontiers in Materials, 2021)
A modified ionic liquid (IL)-based electrolyte, with conventional carbonates as the support solvent and lithium salt as the additive, was designed for a high-voltage electrochemical double-layer capacitor (EDLC). It is found that the employment of carbonate solvents enhances the ionic conductivity and decreases the viscosity of the electrolyte. At the same time, the addition of lithium salt plays a key role in the stabilization of the operating potential window and the modification of the passivation layer on the electrode. As a result, increased specific capacitance, improved cycle stability, and rate capability are demonstrated in the EDLC with an EMI-BF4/LiPF6/PC/DMC electrolyte at the upper voltage of 3 V, in contrast to that with pure IL and IL/carbonate mixture. This study primarily stresses the combination effect of Li salt and organic solvent in an IL electrolyte system for constructing advanced 3 V-class EDLC with excellent overall performance.